The Depiction of Al-BukhÄrÄ«â€™s travels in classical Islamic literature - Usman Ghani (JOURNAL OF QUR'AN AND HADITH STUDIES, 2023)
Travel (riá¸¥la) after the death of the Prophet Muá¸¥ammad, and the geographically disparate locations of his companions made travelling for the acquisition of knowledge, and for the attainment of reliable á¸¥adÄ«á¹¯h an absolute necessity and it was regarded as a key component in the acquisition of this sacred knowledge. The present paper thus, investigates al-BukhÄrÄ« as a major figure in á¸¥adÄ«á¹¯h compilation. Furthermore, it discusses more specifically how he is perceived and exemplified in biographical literature (á¹abaqÄt/tarÄjim). It subsequently, analyses the historical references (kutub al-tÄrÄ«kh), in search of any possible subsidiary details.Â  Finally, by providing a chronological listing of these sources and looking at the included and excluded details, also the possible and acceptable explanations of any incongruities befallen, the present paper will determine whether the information provided is consistent or if it is the subject of embellishment.Keywords: Riá¸¥la, á¸¥adÄ«á¹¯h, al-JÄmiâ€˜ al-á¹¢aá¸¥Ä«á¸¥, á¹abaqÄt, tarÄjim